2017
DOI: 10.1364/ol.42.004004
|View full text |Cite
|
Sign up to set email alerts
|

Fast and accurate modeling of nonlinear pulse propagation in graded-index multimode fibers

Abstract: We develop a model for the description of nonlinear pulse propagation in multimode optical fibers with a parabolic refractive index profile. It consists in a 1+1D generalized nonlinear Schrödinger equation with a periodic nonlinear coefficient, which can be solved in an extremely fast and efficient way. The model is able to quantitatively reproduce recently observed phenomena like geometric parametric instability and broadband dispersive wave emission. We envisage that our equation will represent a valuable to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 26 publications
4
46
1
Order By: Relevance
“…Many questions about graded-index multimode breathers, such as the dynamics with spatial self-imaging effects included [8,12], are still raised to be solved. Recently, the stability of optical solitons in GRIN MMFs was studied in [27] to give a first fundamental understanding of the underlying multimode soliton dynamics by solving a single effective nonlinear Schrödinger equation (NLSE) derived by Conforti et al [28].…”
Section: Introductionmentioning
confidence: 99%
“…Many questions about graded-index multimode breathers, such as the dynamics with spatial self-imaging effects included [8,12], are still raised to be solved. Recently, the stability of optical solitons in GRIN MMFs was studied in [27] to give a first fundamental understanding of the underlying multimode soliton dynamics by solving a single effective nonlinear Schrödinger equation (NLSE) derived by Conforti et al [28].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that the propagation constants of the modes are equally spaced and they have almost identical group velocity [26]. This creates a periodic evolution of the spatial size of the light pattern and therefore induces a periodic evolution of the effective nonlinearity in the propagation direction [27,28]. Recent experiments showed that PRs produced by this GPI can reach detunings from the pump in the order of hundreds of THz [7].…”
Section: Introductionmentioning
confidence: 99%
“…A Gaussian intracavity bandpass filter is assumed with 4 nm spectral bandwidth. We modeled the GIMF segment as a periodically oscillating cubic nonlinearity term to reach manageable computation time, thus discarding the spatial information about the pulse propagation [16,27]. For the GIMF segment, the maximum fiber index contrast is 0.01, the fiber core index is 1.444 and the input beam FWHM is set at 10 m. The gain coefficient is defined as…”
mentioning
confidence: 99%